Injectable Polypeptide Micelles that form Radiation Crosslinked Hydrogels In Situ for Intratumoral Radiotherapy - Schaal, Jeffrey L (J Control Release, 2016)
Intratumoral radiation therapy – ‘brachytherapy’ – is a highly effective treatment for solid tumors, particularly prostate cancer. Current titanium seed implants, however, are permanent and are limited in clinical application to indolent malignancies of low- to intermediate-risk. Attempts to develop polymeric alternatives, however, have been plagued by poor retention and off-target toxicity due to degradation. Herein, we report on a new approach whereby thermally sensitive micelles composed of an elastin-like polypeptide (ELP) are labeled with the radionuclide (131)I to form an in situ hydrogel that is stabilized by two independent mechanisms: first, body heat triggers the radioactive ELP micelles to rapidly phase transition into an insoluble, viscous coacervate in under 2 minutes; second, the high energy β-emissions of (131)I further stabilize the depot by introducing crosslinks within the ELP depot over 24 hours. These injectable brachytherapy hydrogels were used to treat two aggressive orthotopic tumor models in athymic nude mice: a human PC-3M-luc-C6 prostate tumor and a human BxPc3-luc2 pancreatic tumor model. The ELP depots retained greater than 52% and 70% of their radioactivity through 60 days in the prostate and pancreatic tumors with no appreciable radioactive accumulation (≤ 0.1% ID) in off-target tissues after 72 hours. The (131)I-ELP depots achieved >95% tumor regression in the prostate tumors (n=8); with a median survival of more than 60 days compared to 12 days for control mice. For the pancreatic tumors, ELP brachytherapy (n=6) induced significant growth inhibition (p = 0.001, ANOVA) and enhanced median survival to 27 days over controls.